STUDY OF VISCERAL LEISHMANIASIS (KALAAZAR) CASES IN TEHRAN, NECESSITY OF EARLY DIAGNOSIS AND PREVENTION - M. jalali; P. Vosough; S. Ghodsi; Sh. Yousefi (Tehran University of Medical Sciences, 1999)
Thirty eight patients with visceral Leishmaniasis were reviewed, age ranged from 2 months to 10 years, 74% above 3.5 y, with 24% affection in infants (7 to 12 m), with slight male predilection. All the patients had weight loss, splenomegaly and hepatomegaly, 97% with fever, 92% had positive serology and 63% had positive bone marrow findings. A few patients presented with atypical clinical findings and one patient even had no history for fever. In 2 patients both serology and bone marrow were negative, but due to their critical conditions and high indexes of clinical suspicion for this disease, treatment with antimonate (glucantime) was started which was dramatically successful. It was interesting that later in both patients the serology became highly positive. In conclusion this is a disease that firstly could be prevented by strengthening of struggle against phelebotomus and animal reservoirs in affected areas and secondly for early diagnosis and initiation of therapy it is suggested to establish a community setup for medical and laboratory facilities in involved areas.